2013
DOI: 10.1371/journal.pone.0081399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK-3β Rescues the Impairments in Bone Formation and Mechanical Properties Associated with Fracture Healing in Osteoblast Selective Connexin 43 Deficient Mice

Abstract: Connexin 43 (Cx43) is the most abundant gap junction protein in bone and is required for osteoblastic differentiation and bone homeostasis. During fracture healing, Cx43 is abundantly expressed in osteoblasts and osteocytes, while Cx43 deficiency impairs bone formation and healing. In the present study we selectively deleted Cx43 in the osteoblastic lineage from immature osteoblasts through osteocytes and tested the hypothesis that Cx43 deficiency results in delayed osteoblastic differentiation and impaired re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…On the other hand, Cx43 deficiency results in alterations in the mineralization and remodeling phases of fracture healing, and is characterized by delayed expression of osteogenic marker genes, increases in GSK-3beta mRNA and active GSK-3beta, consistent with a pronounced decrease in beta-catenin expression. At the same time, alterations in healing of fractures, in Cx43 deficiency, can be rescued by inhibiting GSK-3beta activity using LiCl [32]. BMSCs play an important role in fracture repair, and BMSC commitment to the chondrogenic or osteogenic lineages improves healing, after homing to the site of fracture, by increasing bone formation [71, 72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Cx43 deficiency results in alterations in the mineralization and remodeling phases of fracture healing, and is characterized by delayed expression of osteogenic marker genes, increases in GSK-3beta mRNA and active GSK-3beta, consistent with a pronounced decrease in beta-catenin expression. At the same time, alterations in healing of fractures, in Cx43 deficiency, can be rescued by inhibiting GSK-3beta activity using LiCl [32]. BMSCs play an important role in fracture repair, and BMSC commitment to the chondrogenic or osteogenic lineages improves healing, after homing to the site of fracture, by increasing bone formation [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Loiselle et al reported that deletion of Cx43 in osteoblasts/osteocytes results in delay of bone formation and bone remodeling, and impairs mechanical properties33 [32], and the mechanisms by which healing is impaired are related to altered activity of GSK-3beta, and therefore beta-catenin expression, during fracture healing 34 [31]. Several signaling pathways have been shown to participate in the regulation of osteogenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs, pre-osteoblasts, osteoblasts, osteocytes, and bone-lining cells all form gap junctions, creating a continuous network and enabling intercellular communication. Of note, FFSS induces conformational changes of Connexin 43 (Cx43) and opens its hemichannels [74, 75]. Deficiency of Cx43 results in lower response of bone to mechanical signals, indicating that Cx43-mediated communication plays a pivotal role in mechanical signal transduction among bone cells.…”
Section: Changed Bone Marrow Microenvironment Under Pathological Condmentioning
confidence: 99%
“…Interestingly, the effect of Cx43 deletion in fracture healing appears to be opposite to that of normal bone, since the RANKL/OPG ratio is decreased, while the levels of the Wnt inhibitor sclerostin (i.e. the product of the Sost gene) are increased and β-catenin is decreased in the fracture [122]. In addition, the effect of Cx43 deletion on fracture healing can be reversed by increasing β-catenin stability [122].…”
Section: Connexins In Bonementioning
confidence: 99%
“…the product of the Sost gene) are increased and β-catenin is decreased in the fracture [122]. In addition, the effect of Cx43 deletion on fracture healing can be reversed by increasing β-catenin stability [122]. These pieces of evidence raise the possibility that Cx43 has distinct roles in bone acquisition/maintenance versus bone healing.…”
Section: Connexins In Bonementioning
confidence: 99%